Alasan Konsumen Tidak Mengadukan Kasusnya serta Bentuk Perlindungan Konsumen Akibat Kosmetik yang Berbahaya Berdasarkan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Maria Grezhella Rihi; Agustinus Hedewata; Helsina Fransiska Pello (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Development of the era in field of trade and industry has led increasingly advanced and innovative products and services created and used by the community. In the era of free trade, export and import opportunities are wide open and have an impact on the entry of products legally or illegally. This study aims to determine the reasons why consumers/victims of the use of cosmetics containing hazardous materials are reluctant to report to BPOM and to determine the form of legal protection for consumers who are harmed due to using cosmetics containing hazardous materials reviewed from Law No. 08 of 1999 concerning Consumer Protection. Aspects that influence consumers not to report cosmetic brands using hazardous materials to BPOM are, consumer reluctance to use cosmetics with hazardous materials comes from combination of individual health problems, increased knowledge and awareness, ethical considerations, trust in regulations, and the influence of social and environmental factors. The circulation of cosmetic products containing hazardous materials will harm consumers, in this case business actors have certainly violated the Consumer Protection Law. These forms of legal protection create a just and orderly society by balancing individual freedom with the need for regulation and protection against various potential losses.